Strategy of Sustainability and Green Tourism Innovation in Tengah Sawah Gubug Tourism - Lestari, Putri; Mistriani, Nina (Eastasouth Institute, 2025)
Tourism destinations often struggle with sustainability and innovation challenges, as observed in Wisata Tengah Sawah Gubug, Grobogan, Central Java. This research employs a qualitative approach to explore the issues of under-maintained facilities, limited accessibility, and lack of innovation, which have contributed to declining visitor numbers. Data were collected through interviews with visitors and management, field observations, and document analysis. The findings reveal several critical issues: inadequate facility maintenance, dependency on seasonal visitors, and a lack of innovative attractions. These factors undermine the destination's competitiveness and sustainability. To address these challenges, the study recommends routine maintenance, the introduction of innovative attractions, improved accessibility, and collaborative funding strategies involving private sector partnerships. This study concludes that the application of an approach focused on sustainability and innovation can transform Wisata Tengah Sawah Gubug into a model for green and rural tourism development through environmental practices, community involvement, innovative attractions, policy frameworks.